Regional Trends and Pattern in Milk Production in Maharashtra State - Nagrale, Bulbul G; Datta, K K; Ghule, Avinash K (Indian Journal of Dairy Science, 2012)
The state of Maharashtra has maximum area under rainfed even though it is one of the leading state in terms of livestock population and milk production in the country. All the regions of Maharashtra shows negative growth in local cow population and positive growth in both the crossbred and buffalo population except Konkan. Buffalo contributes maximum to the milk production in the state followed by crossbred and local cow, except in Vidarbha and Marathwada region, where local cow contributes more. The significant contributor to the increase in milk production in the state is increase in inmilk population followed by increase in milch population. The major descript breeds found in the state of local cow are Red Kandhari, Khillari and buffalo breeds are Murrah and Pandharpuri.